Effect of Excess Concentration of Secondary Ligand on Stability of Mixed Ligand Complexes - Patel, K.P.; Patel, D.R.; Pabreja, D.S.; Sharma. J.J. Vora, Sangita; Joshi, J.D. (Asian Journal of Chemistry, 2010)
The formation constants of ternary complexes MAL where M = Ni(II), Cd(II) or Zn(II), A = 2,2' -bipyridyl amine as primary ligand and L = 1,2-diaminopropane or ethylene diamine have, been determined in aqueous solution by potentiometric method at constant ionic strength, μ= 0.2 M at 30 ± 0.1 °C. The stability of the complexes is explained in terms of M→L π iriteraction, size of the chelate ring and steric factors. The effect of higher molar concentration of secondary ligand (1 : 1 : 2.5) on stability constants of complexes is compared with optimum molar concentration of L (1 : 1 : 1).